Teaching strategies adopted in coach education programs: analysis of publications from 2009 to 2015 (Journal of Physical Education (Maringá), 2018)
In order to overcome the limitations and negative perceptions often addressed to coach education programs, the sports coaching literature has offered important contributions for its improvement. Thus, through analyzing scientific articles published between 2009 and 2015, this study aimed to identify the teaching strategies adopted in small-scale, large-scale, and university-based programs. An automatic search for articles was conducted in the following databases: PUBMED, SCOPUS, Web of Science, PyscNET, and SPORTDiscus. Manual search was conducted in two non-indexed peer-reviewed journals. Afterwards, 731 articles were found and 16 were selected by applying the established criteria. The results indicated that most of the studies selected took place in a university-based context. In relation to the teaching strategies adopted, we verified a common intent to engage coaches in group discussions and reflection activities. Based on the articles analyzed, we suggest that the teaching strategies adopted in coach education programs indicate a trend towards learner-centered approaches (coach-centered), meeting the international guidelines for the improvement and effectiveness of these endeavors.